Solution of boundary-value problems for elliptic equations in the space of distributions - Lopushanskaya, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We extend the well-known approach to solution of generalized boundary-value problems for second-order elliptic and parabolic equations and for second-order strongly elliptic systems of variational type to the case of a general normal boundary-value problem for an elliptic equation of order2m. The representation of a distribution from (C ∞ (S))’ is established and is usedfor the proof of convergence of an approximate method of solution of a normal elliptic boundary-value problem in unnormed spaces of distributions.